Influence of the Relationship between Purchase Intentions and Tourism Behavior of Environmentally Friendly Products in Indonesia Using the PLS SEM Method - Putri Alfia Julia Lingga; Zunan Setiawan; Lilik Wahyudi; Agus Siswanto; Aftoni Sutanto (Budapest International Research and Critics University, 2022)
This study intends to investigate the exogenous effects of experiential attitudes, instrumental attitudes, injunctive norms, descriptive norms, and self-perception control on environmentally conscious buying intentions. In addition, this study examines the elements that influence purchasing behavior by analyzing knowledge, behavioral meaning, environmental restrictions, and habits. The model adopted by the researcher measures environmentally conscious customer behavior. Using a partial least squares structural equation modeling (PLS-SEM) technique, random data from 517 respondents was obtained to test the hypothesis. According to PLS results, all independent variables influence green purchasing intentions and green consumer behavior. There are research results that imply generalizations, despite the fact that the survey was conducted in multiple cities in Indonesia that may not be representative of the entire country. The outcomes of research can assist marketers in comprehending environmentally conscious consumer behavior and developing appropriate plans and techniques to meet the demands of modern marketing strategies. This research assessed environmentally conscious purchasing practices in Indonesia. Based on empirical evidence, the study's validity in judging environmentally friendly behavior, particularly in Indonesia's major cities, is a fast-rising economy that is favorable for investment. Even though there has been a lot of research on green purchasing, the habits and importance of being green or friendly environmentally haven't been taken into account when measuring green purchasing.